Nuclear spin dynamics in nuclear-ordered solid ³He in the low field phase - Matsushita, T.; Nomura, R.; Hensley, H.H.; Shiga, H.; Mizusaki, T. (Физика низких температур, 1996)
Pulsed NMR experiments have been performed on U2D2 solid ³He with a single domain in high fields. The free induction signal decayed rapidly under certain conditions. The rapid decay was attributed to the onset of an instability of uniform precession. We propose a model for the instability due to the self-induced emission from the upper-mode to lower-mode magnon branch, which is similar to the Suhl instability in electronic ferromagnets. Under stable conditions of the spin motion, we observed the tipping-angle-dependent frequency shift and multiple spin echoes, which agrees well with Namaizawa’s theory.